Implementasi Sistem Inventori pada Prodi Informatika Universitas Kristen Petra - Richard Putra Sugijanto; Henry Novianus Palit; Leo Willyanto Santoso (Jurnal Infra, 2020)
Petra Christian University Informatics Study Program is one of the educational institutions which one of the activities to carry out an inventory of items which includes submission, purchase, recording, and distribution / delivery of items both for the purposes of supporting teaching and learning activities and for the needs of employees in carrying out their work in serving students and lecturers, and its reporting. So far there has not been an inventory system, especially in laboratories used by Informatics Study Programs. The data collection and reporting process is still done manually which requires a long time in completing each work. Errors sometimes occur in the calculation and recording of items. Items are often moved so that they forget where they are. Seeing the problems that occur, then made a computerized inventory system to simplify and speed up the data collection process, and the process of reporting inventoryThe software developed is a web-based inventory system. This system is also adjusted to the results of the analysis of the existing system with several additional features to adjust the needs of the laboratory. The web system was developed using the serveride PHP programming language as well as several supporting libraries such as clientide css, javascript in the form of bootstrap, datatables, and jQuery.The final results of software development include the movement of items that occur in laboratories, such as input data of items, lending, returning and moving items.